Korelasi Pemanfaatan Media Pembelajaran Digital dengan Hasil Belajar Mata Pelajaran Pendidikan Agama Islam di SMPN 4 Payakumbuh - Faizatur Rafi’ah; Zulfani Sesmiarni (Lembaga Yasin AlSys, 2026)
Although the use of digital learning media in Islamic Religious Education (PAI) has been widely studied, research specifically analyzing its relationship with PAI learning outcomes in schools that implement digital classes remains limited. This study aims to analyze the relationship between the use of digital learning media and the PAI learning outcomes of students in the Grade VIII Digital class at SMP Negeri 4 Payakumbuh. This study employed a quantitative approach with a correlational design and involved 95 students selected through total sampling. Data were collected using a questionnaire to measure the level of digital learning media use and documentation of students’ PAI learning outcome scores. The data were analyzed using descriptive statistics, prerequisite analysis tests, the Spearman rank correlation test, and simple regression with the assistance of IBM SPSS Statistics version 27. The results showed that the use of digital learning media was in the good category but had no significant relationship with PAI learning outcomes, as indicated by a correlation coefficient of 0.073 and a significance value of 0.481 (p > 0.05). The R² value of 0.000 also indicated that the use of digital learning media did not contribute to variations in students’ learning outcomes. These findings confirm that a high level of digital media use is not directly associated with improved PAI learning outcomes because learning outcomes may be influenced by various other factors. This study enriches research on digital learning in the context of Islamic Religious Education and implies the need for teachers to integrate digital media with interactive and student-centered learning strategies. Future research is recommended to examine other variables that may influence PAI learning outcomes.